Electrophysiological correlates of direct versus indirect semantic priming in normal volunteers - Weisbrod, Matthias; Kiefer, Markus; Winkler, Sabine; Maier, Sabine; Hill, Holger; Roesch-Ely, Daniela; Spitzer, Manfred (Brain research. Cognitive brain research, 1999)
The N400 component of event related potentials (ERP) was studied in 27 right-handed healthy subjects in a speeded lexical decision task. The semantic distance between primes (always words) and targets (50% words, 50% non-words) was systematically varied. Prime-target relations included directly related words (hen-egg), indirectly related words (lemon-sweet), and non-related words (sofa-wing). ERPs were recorded from 20 scalp electrodes positioned according to the international 10-20 system. The N400 reflected semantic distance with the most negative and latest N400 peak in the non-related condition, the least negative and earliest N400 peak in the direct condition and the peak in the indirect condition in-between. Hence, N400 priming effect in the indirect condition was obtained in the absence of strong sentential constraints and even though the mediating word was physically not present.
Available online 7 January 2000
Gesehen am 08.06.2021